Investigation of superfluidity in ultra-short flows : effect of time-lags in transport phenomena - Peyman Tavallali (2011)
In this thesis, an investigation of the phase-lagged formulation of the high-temperature model of superfluidity is presented. Also, as a consequence of the physical idea behind the latter, a new model for heat transfer at nano-scale is presented. In general, the thesis is about the effect of the time delay in the transport of the energy and momentum in transport phenomena formulations. These time delays depict themselves in the functional form of their corresponding differential equations. As a result, the mathematics behind the modeling is nothing but subclasses of delay differential equations, both partial and ordinary.